The silent feminist America's first women directors - Slide, Anthony; Goodman, Jeffrey; Direct Cinema Ltd. (New York: Insight Media, 1994)
An examination of the achievements and innovations of American women silent film directors
Copy available in DVD format
Photography, Melinda Sue Gordon ; editor, Terry Finch ; narrator, Jane Wyatt ; music, Capitol Production Music, Ole Georg
Keywords: Motion pictures -- Production and direction; Women motion picture producers and directors